Disappearance of Plaque Following Treatment with Antioxidants in Peyronie’s Disease Patients—A Report of 3 Cases - Gianni Paulis; Giovanni De Giorgio (Clinics and Practice, 2022)
Peyronie’s disease (PD) is a fibrotic disorder of the penile tunica albuginea. To date, only a few cases of recovery from PD following medical treatment have been reported in the literature. In this article, we describe three new cases of PD where patients achieved complete resorption of plaque following multimodal antioxidant treatment. In all three cases, treatment included the following antioxidants: bilberry, propolis, ginkgo biloba, silymarin, and vitamin E. Only in case nos. 1 and 2 did we also use the following antioxidant substances: L-carnitine, coenzyme Q10, and Boswellia. In all three cases, we also used a local therapy with diclofenac gel. Only in case no. 2 did we also use periodic perilesional injections with pentoxifylline. Although the sample of cases presented here was small, these patients incontrovertibly experienced complete plaque disappearance and recovery (in one case, only after a short course of treatment). Therefore, it is our conviction that urologists may find our experiences of considerable interest in their clinical practices.